Synthesis of a recyclable and efficient Pd(II) 4-(2-pyridyl)-1,2,3-triazole complex over a solid periodic mesoporous organosilica support by ``click reactions'' for the stille coupling reaction - Sharma, Priti; Singh, A. P. (RSC Advances, 2014)
A highly efficient, reusable B-PMO-TZ-Pd(II) catalyst was synthesized by anchoring 4-(2-pyridyl)-4-(2-pyridyl)-1,2,3-triazole ligand over the surface of an organo-functionalized benzene support containing periodic mesoporous organosilica (B-PMO) via ``click reaction'' and the subsequent complexation with PdCl2. B-PMO materials with uniform hexagonal arrangements were prepared using C-16 alkyl trimethyl ammonium bromide [CTAB] surfactant under basic conditions. The physiochemical properties of the functionalised catalyst were analysed by elemental analysis, ICP-OES, XRD, N-2 sorption, TGA & DTA, solid state C-13, Si-29 NMR spectra, FT-IR, XPS, UV-vis, SEM and TEM. XRD and N-2 sorption revealed the morphological and textural properties of the synthesized catalyst, confirming that ordered mesoporous channel structure was retained even after the multistep synthetic procedure. The (100), (110) and (200) reflections in B-PMO are evidence of its good structural stability and the existence of long range order. The TGA-DTA results reveal that the synthesized catalyst B-PMO-TZ-Pd(II) was thermally stable, even at high temperature. The organic moieties anchored over the surface of B-PMO were demonstrated by solid state C-13 NMR and FT-IR spectroscopy. Solid state Si-29 NMR spectroscopy provides information about the degree of functionalization of the surface silanol group. The electronic environment and oxidation state of Pd in B-PMO-TZ-Pd(II) were monitored by XPS and UV-visible techniques. Moreover, the morphologies and topographic information of the synthesized B-PMO-TZ-Pd(II) catalyst were confirmed by SEM and TEM analyses. The catalytic properties of the catalyst for the Stille coupling reaction were screened, and higher catalytic activities with high TONs were observed. The anchored solid B-PMO-TZ-Pd(II) catalyst can be recycled efficiently and reused several (four) times without a major loss in reactivity.

Synthesis and characterization of nanoporous silica SBA-15 diaminocyclohexane and its application in removal of Cu(II) and Ni(II) from aqueous solution - Sreenu, Bhogineni; Sharma, Priti; Seshaiah, Kalluru; Singh, A. P. (Desalination and Water Treatment, 2016)
A new nanoporous 1,2-diaminocyclohexane-functionalized SBA-15 (Dach@SBA-15) silica sorbent was prepared. The structure and physicochemical properties of the material were characterized by elemental analysis, X-ray diffraction, transmission electron microscopy (TEM), scanning electron microscopy, FT-IR spectroscopy, nitrogen adsorption-desorption isotherms and thermogravimetric analysis. TEM image clearly showed the sheet-like structure of Dach@SBA-15. The organic functional groups were successfully grafted onto the SBA-15 surface and the ordering of the support was not affected by the chemical modification. The Dach@SBA-15was used as a sorbent for removal of Cu(II) and Ni(II) from aqueous solution. Experimental parameters like effect of pH, contact time and metal ion concentration were studied and optimized. The adsorption isotherm data fitted well to Langmuir isotherm model and the monolayer adsorption capacity values for Cu(II) was 90.09 and for Ni (II) was 84.03 mg/g at 303 K. The experimental kinetic data fitted very well to the pseudosecond- order model. The Dach@SBA-15 could be used as a sorbent for removal of Cu(II) and Ni(II) from aqueous medium.
Keywords: Adsorption; BET; FAAS; FT-IR; Heavy metals; Nanoporous silica

Synthesis of new hybrid sorbent 2-mercaptobenzaldehyde SBA-15 and its application in solid phase extraction of Cd(II) from water and food samples - Sreenu, B.; Imran, K.; Seshaiah, K.; Sharma, Priti; Singh, A. P. (Analytical Methods, 2016)
In this paper, a new mesoporous hybrid material was fabricated by anchoring 2-mercaptobenzaldehyde (2MB) onto the surface of SBA-15. The adsorbent (2MB-SBA-15) was characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), nitrogen adsorption-desorption isotherm measurements and thermogravimetric analysis (TGA) and applied as a sorbent in the preconcentration of Cd(II) in water samples and food samples. The effect of various analytical parameters such as pH, dose of sorbent, amount of eluent, sample flow rate and interfering ions was investigated. The preconcentration capacity of the prepared material under optimized conditions for Cd(II) was 0.94 +/- 0.01 mmol g(-1). The Cd collected onto the sorbent was eluted out with 10 mL of 1 M HNO3 and determined by AAS. The LOD, LOQ and preconcentration factor of the present method were found to be 6.93 x 10(-6), 1.21 x 10(-5) mM and 100, respectively. The relative standard deviation for four preconcentration experiments was found to be <= 5%.

Synthesis of heterogeneous Ru(II)-1,2,3-triazole catalyst supported over SBA-15: application to the hydrogen transfer reaction and unusual highly selective 1,4-disubstituted triazole formation via multicomponent click reaction - Sharma, Priti; Rathod, Jayant; Singh, A. P.; Kumar, Pradeep; Sasson, Yoel (Catalysis Science & Technology, 2018)
In the present study, we demonstrate a simple and efficient method for ligand formation and covalent anchoring to a heterogeneous support via click reaction. The complex tris(triphenylphosphine) ruthenium(II) dichloride [RuCl2(PPh3)(3)] anchored over the click modified ligand of SBA-15 forms a new highly efficient heterogeneous SBA-15-Tz-Ru(II) TPP catalyst. Solid state C-13, Si-29, and P-31 CP-MAS NMR spectra provide evidence for the formation of the heterogeneous catalyst. SBA-15-Tz-Ru(II) TPP catalyst was screened for the multicomponent click cycloaddition reaction in water medium as a green solvent and it exhibited unusual and excellent selectivity for the formation of 1,4-disubstituted triazole product under mild reaction condition. In addition, SBA-15-Tz-Ru(II) TPP catalyst also catalyzed the hydrogen transfer reaction of various carbonyl compounds with excellent catalytic activity to give the corresponding alcohols. The heterogeneous catalyst can be recycled and reused several times (five) without a loss in reactivity.